0.5 V, nW-Range Universal Filter Based on Multiple-Input Transconductor for Biosignals Processing - Khateb, Fabian; Kumngern, Montree; Kulej, Tomasz; Akbari, Meysam; Stopjakova, Viera (Sensors (Basel, Switzerland), 2022)
This paper demonstrates the advantages of the multiple-input transconductor (MI-Gm) in filter application, in terms of topology simplification, increasing filter functions, and minimizing the count of needed active blocks and their consumed power. Further, the filter enjoys high input impedance, uses three MI-Gms and two grounded capacitors, and it offers both inverting and non-inverting versions of low-pass (LPF), high-pass (HPF), band-pass (BPF), band-stop (BS) and all-pass (AP) functions. The filter operates under a supply voltage of 0.5 V and consumes 37 nW, hence it is suitable for extremely low-voltage low-power applications like biosignals processing. The circuit was designed in a Cadence environment using 180 nm CMOS technology from Taiwan Semiconductor Manufacturing Company (TSMC). The post-layout simulation results, including Monte Carlo and process, voltage, temperature (PVT) corners for the proposed filter correlate well with the theoretical results that confirm attractive features of the developed filter based on MI-Gm.
Keywords: low-voltage low-power; biosignals processing; OTA; universal filter; multiple-input MOS transistor